Efficiency of betaadrenoblockers in pregnant women with idiopathic ventricular tachycardia - E. A. Pripachkina; A. P. Filev; A. V. Govorin; N. V. Mukha; N. A. Sokolova; P. V. Vasilenko (Acta Biomedica Scientifica, 2018)
The aim of the research: to assess neurovegetative status according to the variability of the heart rhythm in pregnant women with idiopathic ventricular extrasystole and to estimate the efficiency of beta-adrenoblockers in this category of patients. Materials and methods. To study the variability of the heart rhythm daily ECG recording was made in 38 pregnant women with ventricular arrhythmias. Control groups consisted of somatically healthy pregnant and non-pregnant women. Patients with sympathicotonia detected during Holter ECG monitoring were given metoprolol in a dose of 25 mg per day. The efficiency of the treatment was assessed by Holter ECG monitoring one week after the start of therapy. Results. It was found that the decrease of the main time and spectral indices of cardiac rhythm variability is characteristic for pregnant women with idiopathic ventricular arrhythmias V gradation by Ryan. In addition in this category of patients against the background of a lower total cardiac rhythm variability there was a significantly greater contribution of central neurohumoral influences (VLF%) and on the contrary - a smaller contribution of peripheral vagal influences (HF%). In control Holter ECG monitoring after a week use of metoprolol ventricular tachycardia was not recorded. Conclusion. In pregnant women with ventricular extrasystole V gradation by Ryan overexertion of adaptive processes in the form of a predominant influence on the regulation of the rhythm of the heart of higher vegetative centers and moderate sympathicotonia were detected. A small doses beta-adrenoblockers therapy showed high efficiency in the treatment of ventricular tachyarrhythmias in patients with autonomic dysfunction.